Role of Drug-coated Balloons in Small-vessel Coronary Artery Disease - Michael Megaly; Marwan Saad; Emmanouil S Brilakis (US Cardiology Review)
Percutaneous coronary intervention of small-vessel coronary artery disease (SVD) remains challenging due to difficulties with device delivery and high restenosis rate, even with the use of newer-generation drug-eluting stents. Drug-coated balloons represent an attractive emerging percutaneous coronary intervention option in patients with SVD. Potential advantages of drug-coated balloons in SVD include enhanced deliverability because of their small profile, avoidance of foreign-body implantation, and shorter duration of dual antiplatelet therapy.